2002
DOI: 10.1076/ceyr.25.5.287.13496
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green-mediated photothrombosis as a new technique of treatment for persistent central serous chorioretinopathy

Abstract: Photothrombosis using low-intensity 810 nm light to direct laser energy continuously at the active leakage sites after intravenous ICG infusion induced rapid VA recovery in patients with persistent CSC; accordingly, restoration of the macular architecture was evidenced on OCT, and no recurrence was noted 12 months after IMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…It typically affects young and middle-aged adults and is usually associated with good visual prognosis [2, 3]. The diagnosis is confirmed by fluorescein angiography and indocyanine green (ICG) angiography, which reveal the site of serous fluid leakage from RPE into the subretinal space and identify choroidal hyperpermeability and possible ischemia [2, 4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…It typically affects young and middle-aged adults and is usually associated with good visual prognosis [2, 3]. The diagnosis is confirmed by fluorescein angiography and indocyanine green (ICG) angiography, which reveal the site of serous fluid leakage from RPE into the subretinal space and identify choroidal hyperpermeability and possible ischemia [2, 4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…In a case series, IMP produced favourable results in patients with persistent CSC, but adverse events, such as mild and transient retinal whitening and retinal capillaries occlusion, occurred in three out of the eleven patients [40]. The severe retinal damage reported in the case of persistent CSC treated with IMP prompted the warning for potential severe adverse events [41].…”
Section: Discussionmentioning
confidence: 99%
“…In eyes that show diffuse oozing, laser photocoagulation may not be a suitable treatment modality because localization of the leaking point is difficult. Photodynamic therapy (PDT) with verteporfin, which causes less thermal damage, has resulted in beneficial visual outcomes in most studies of patients with chronic CSC [5][6][7]. However, several studies have shown that conventional PDT, traditionally used to treat choroidal neovascularization or polypoidal choroidal vasculopathy, may cause RPE atrophy, choroidal ischemia, and transient reduction in macular function [5,8,9].…”
Section: Introductionmentioning
confidence: 99%